Modeling Cu(II) Binding to Peptides Using the Extensible Systematic Force Field - Faina Ryvkin; Frederick T. Greenaway (Bioinorganic Chemistry and Applications)
The utility of the extensible systematic force field (ESFF) was tested for copper(II) binding to a 34-amino-acid Cu(II) peptide, which includes five histidine residues and is the putative copper-binding site of lysyl oxidase. To improve computational efficiency, distance geometry calculations were used to constrain all combinations of three histidine ligands to be within bonding distance of the copper and the best results were utilized as starting structures for the ESFF computations. All likely copper geometries were modeled, but the results showed only a small dependence on the geometrical model in that all resulted in a distorted square pyramidal geometry about the copper, some of the imidazole rings were poorly oriented for ligation to the Cu(II), and the copper-nitrogen bond distances were too long. The results suggest that ESFF should be used with caution for Cu(II) complexes where the copper-ligand bonds have significant covalency and when the ligands are not geometrically constrained to be planar.